2019
DOI: 10.1080/02652048.2019.1585982
|View full text |Cite
|
Sign up to set email alerts
|

β-carotene and α-tocopherol coencapsulated in nanostructured lipid carriers of murumuru (Astrocaryum murumuru) butter produced by phase inversion temperature method: characterisation, dynamicin vitrodigestion and cell viability study

Abstract: Hydrophobic bioactives can be more easily incorporated into food and have their bioavailability enhanced if nanostructured lipid carriers (NLC) are used as carriers. In the present study, betacarotene-loaded NLC were produced by low emulsification using murumuru butter and a mixture of Span 80 and Cremophor RH40 as surfactants. Their average diameter was 35 nm and alpha-tocopherol was required to protect the encapsulated b-carotene. Besides the evaluation of their physicochemical stability, NLC were submitted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…Pereira et al (2019) found similar results to those obtained in the present study for the composition of murumuru butter. Due to its chemical composition, being rich in unsaturated fatty acid, this butter showed potential properties for the development of nanoparticles (Gomes et al, 2019) and biocosmetics (Silva et al, 2014). Bacuri butter presented palmitic and oleic acids as its major fatty acids, corroborating with the results of the supplier report.…”
Section: Discussionmentioning
confidence: 99%
“…Pereira et al (2019) found similar results to those obtained in the present study for the composition of murumuru butter. Due to its chemical composition, being rich in unsaturated fatty acid, this butter showed potential properties for the development of nanoparticles (Gomes et al, 2019) and biocosmetics (Silva et al, 2014). Bacuri butter presented palmitic and oleic acids as its major fatty acids, corroborating with the results of the supplier report.…”
Section: Discussionmentioning
confidence: 99%
“…SLNs and NLCs prepared using this method have been reported to have small PSs, narrow size distribution, and excellent stabilities [ 118 , 119 ]. For example, NLCs loaded with β-carotene and α-tocopherol had a PS of 35 nm [ 120 ]. This method requires little energy input and does not require organic solvents.…”
Section: Methods For Slns and Nlcs Preparationmentioning
confidence: 99%
“…Current literature reports use various fabrication methods for NLCs including, highpressure homogenization at high or low temperatures (including cold homogenization and hot homogenization) [335], solvent emulsification-diffusion techniques [331], supercritical fluids (supercritical fluid extraction of emulsion) [336], solvent emulsification evaporation [335], solvent displacement [135], solvent diffusion [337], phase inversion [338,339], melt emulsification [340], sonication [334], spray-drying [340,341], and solvent evaporation [335].…”
Section: Nanostructured Lipid Carriers (Nlcs)mentioning
confidence: 99%